Elementos para romper com a genética inquisitorial no processo penal do Brasil - Moura, Edvaldo Pereira de (2022)
Through the thesis to which we have proposed, and under the guidance from professor, Nereu José Giacomolli, we aim to offer a plain argumentative position about the indispensability of the disruption with the inquisitive genetics of the Brazilian criminal procedural law, which was inspired by the fascist criminal code, Codice Rocco, from 1930, written by the theoretician Vincenzo Manzini, aiming to be able to implement, for real, a humane and democratic Criminal Justice system, founded on the statutes of the Brazilian Constitution of 1988, and on the treaties and conventions pleaded by Brazil, with which we completely agree. Let it be registered that, for the achievement of such propositions, we have to take possession of the knowledge and experience of the criminalists and criminal procedural authors with avant-garde opinions, supporters of the criminal minimalism and of the legitimate guarantism. At last, we acknowledge that, for the success of this difficult mission, we need to be armed both in the sphere of legislation, by mitigating the repressive rage, and in the one of the jurisdiction, with humane, correct and fair decisions. In the scope of Criminal Law, we have an actual legislative inflation, with the typification of criminal norms with minimum or dubious offensive potential and, within the scope of jurisdiction, we need judges who act and work with a humanistic and democratic formation and, above all, capable, competent, courageous and impartial.